Enhancing Placements in Educational Institutes: A Novel Approach - Joshi, Ajinkya; Shahabadkar, Pramod; Hippalgaonkar, Amrutha (Journal of Engineering Education Transformations, 2025)
The ABC analysis is an established inventory control technique in the industry wherein the available inventory is divided into three categories. It is similar to the Pareto principle and provides a mechanism to segregate the material into different categories based on their values to the industries. This study presents a novel approach of extending the concept of ABC analysis to the companies visiting the institutes for conducting the campus interview. The primary objective of this study was to enhance the quality and number of placements in the institute by classifying the industries as per the ABC analysis. The data of 268 companies visiting the institute over a period of eight years was documented and analyzed. After careful deliberations, a formula was established to determine the value of each company offering placements. The percentage value obtained for every company was used to segregate the companies into A, B and C categories. For calculations, the study has considered only the number of placements and average package offered by the visiting companies. Thereafter certain initiatives were undertaken by the institute for engaging with the industries. The motive was to enhance the quality of placements and to increase the industry-institute interactions in the institute. It was observed that the implementation of various initiatives led to an increase in the number of placements, average and maximum package. Within a year, the placements increased by 121 while the maximum package increased to 4.6 Lakhs. Pro-active engagement with the ‘A’ category companies have also resulted in additional benefits such as scholarships for needy students, increase in internships for students and increase in footfall of the industry experts and establishment of Centre of Excellence. The present study is a unique attempt to enhance the quality and number of placements in educational institutions. It represents a logical extension of a simple and commonly used technique in a different domain. This approach can be applied to any educational institute with suitable modifications for increasing the industry-institute interactions.